Twenty-third Inter-Sessional Meeting of Heads of Governement [i.e. Government] of the CARICOM, Suriname, 8-9 March (Government of Suriname [Paramaribo], 2012)
Photographic album of the 23rd Inter-Sessional Meeting of the Heads of Government of the Caribbean Community, Suriname, 8-9 March 2012.
Keywords: PHOTOGRAPHS